Determination of Physico-Chemical and Microbiological Characterization of Recycled, Open and Eutrophicated Lake Water Grabs and Assessment of its Effects on A Vertebrate System Zebra Fish (Danio rerio) - P. Raj, Mathews; Satishchandra, Nalini (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The objective of the study was to assess Mallathahalli Lake for physico-chemical characters and microbial characters and to evaluate its effects on zebra fish (Danio rerio) a vertebrate model. Bangalore is a metropolitan and capital city of the state of Karnataka in India, it is considered to be the fastest growing Information technology and Biotechnology hub of the world. In contrast with the same the city is subjected to continuous development through anthropogenic activities where in it has lost most of its wetlands like lakes and the existing water bodies are exploited to the highest order the resultant of which is seen through the spread of diseases and loss of existing natural aquatic bodies and loss of ecosystem. In the present study grab water samples were collected from three distinct sampling stations of Mallathahalli Lake, Bangalore, India and assessed for various physical and chemical parameters betwixt December 2014 and February 2015; Microbiological evaluation was also extrapolated for the lake betwixt the same period. The average values recorded for the physical parameters like pH and temperature for Recycled, Open and Eutrophicated lake water was found to be within the limit. The average values recorded for the chemical parameters from the three sampling stations were found to be within the standards set by World Health Organization (WHO) for drinking water quality. The DO, BOD and COD values were found to be varying in the three different sampling stations implicating organic pollution. Bacteriological examination of water indicated high microbial activity and proved water to be unfit for human consumption. The effect of the water quality was supported by heart beat count and acetyl choline esterase activity which was established in zebra fish a vertebrate model. Zebra fish analysis concluded recycled water to be of better quality when compared to eutrophicated and open water system.